The Pantheon+ analysis: Improving the redshifts and peculiar velocities of Type Ia supernovae used in cosmological analyses. (11th October 2022) - Carr, Anthony; Davis, Tamara M.; Scolnic, Dan; Said, Khaled; Brout, Dillon; Peterson, Erik R.; Kessler, Richard
Abstract: We examine the redshifts of a comprehensive set of published Type Ia supernovae, and provide a combined, improved catalogue with updated redshifts. We improve on the original catalogues by using the most up-to-date heliocentric redshift data available; ensuring all redshifts have uncertainty estimates; using the exact formulae to convert heliocentric redshifts into the Cosmic Microwave Background (CMB) frame; and utilising an improved peculiar velocity model that calculates local motions in redshift-space and more realistically accounts for the external bulk flow at high-redshifts. We review 2607 supernova redshifts; 2285 are from unique supernovae and 322 are from repeat-observations of the same supernova. In total, we updated 990 unique heliocentric redshifts, and found 5 cases of missing or incorrect heliocentric corrections, 44 incorrect or missing supernova coordinates, 230 missing heliocentric or CMB frame redshifts, and 1200 missing redshift uncertainties. The absolute corrections range between 10^-8 ≤ Δ z ≤ 0.038, and RMS (Δ z) 3× 10^-3 . The sign of the correction was essentially random, so the mean and median corrections are small: 4× 10^-4 and 4× 10^-6 respectively. We examine the impact of these improvements for H_0 and the dark energy equation of state w and find that the cosmological results change by Δ H_0 = -0.12 km s^-1Mpc^-1 and Δ w = 0.003, both significantly smaller than previously reported uncertainties for H_0 of 1.0 km s^-1Mpc^-1 and w of 0.04 respectively.